Digital marketing strategy for generating sales leads – case study of Hilti - Báša, Petr; Karlíček, Miroslav, 1979-; Jindrák, Jiří; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
This research endeavors to identify the key success factors of digital marketing communication strategy with the goal of generating leads for Hilti strategic services. To reach the goal of the study, qualitative research method in the form of semi-structured interviews with marketing and sales managers was used. Among the outcomes, we have identified the potential for greater integration between the sales and marketing departments in several areas, creating awareness as the prerequisite for lead generation, the focus of quality of leads instead of quantity, clearly defined and transparent lead follow-up process and delivery of comprehensive content integrated across all channels. Two internal barriers hindering an effective lead generation process were discovered. All the outcomes are addressed in the managerial recommendations section of the study.
Vedoucí práce: Miroslav Karlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses